Micronutrient Deficiency and Wernicke’s Encephalopathy in the Setting of Over the Counter Transcutaneous Multivitamin Patch Use Following Bariatric Surgery - Hisham Mohammed Babu, MBBS; Andrew J. Spiro, MD; Thanh D. Hoang, DO; Mohamed K.M. Shakir, MD (AACE Clinical Case Reports)
Background/Objective: Thiamine deficiency, which may occur following bariatric surgery, can lead to the development of Wernicke’s encephalopathy (WE). This case report describes a patient developing WE postbariatric surgery, due to the use of over-the-counter transcutaneous multivitamin patch rather than recommended vitamin tablets. Case Report: A 61-year-old female presented with 45 pounds of weight gain over the past year with a body mass index of 39.58 kg/m2. She underwent lifestyle modification and treatment with dulaglutide with limited success. After evaluation and counseling, the patient underwent Roux-en-Y gastric bypass surgery and was prescribed thiamine, cholecalciferol, vitamin B12, and multivitamin tablets postoperatively. Eight months later, she presented to the emergency room with confusion, bilateral lower extremity weakness, paresthesia, and ataxia. Neurological examination revealed disorientation, nystagmus, and bilateral lateral rectus palsies. She reported using transcutaneous multivitamin patches instead of the recommended oral supplementation. The clinical features, low serum thiamine level of 1.28 μg/dL (reference 2.5–7.5 μg/dL), and resolution of symptoms following supplementation confirmed the diagnosis of WE. Discussion: Obesity often predisposes individuals to multiple nutritional deficiencies. It is critical that these patients take adequate vitamin supplementation before and after bariatric surgery. Thiamine deficiency can present as WE due to inappropriate supplementation such as use of a transcutaneous patch as seen in our patient. Conclusion: Adequate nutritional counseling and supplementation before and after bariatric surgery is required to prevent complications. Transcutaneous patch as a mode of multivitamin supplementation is questionable in its current state and should be avoided.